Dampak Penggusuran Di Area Roxy Jember Terhadap Pedagang Kaki Lima - Jane Sabathani Putri; Rizaldy Andy Wijaya; Vanessa Marcia Hitipeuw (Universitas Katolik Widya Karya Malang, 2023)
Street vendors are traders who usually display their wares and sell by utilizing public spaces in the community. Therefore, public space certainly becomes something meaningful for these street vendors. However, unfortunately, as a street vendor who has never officially obtained permission from the government to have the freedom to use this public space as their selling stall, the potential for eviction will continue to exist and threaten their existence and the activities they carry out. Therefore, it is necessary to have concrete solutions prepared, provided and offered by the government so that they can regain their rights as part of society to use and access public spaces or the environment in order to make a living and survive. The existing solutions must be in the form of things and points that benefit any party and not just one side, but the entire community and the government and the country itself. In this case, the government is significantly trying to find a solution and so are the street vendors themselves to prepare life defense strategies both in the social and economic fields so as to avoid a decline or impact that can be caused if at any time evictions or relocations are carried out.